Valencia y los aragoneses en la baja edad media: la ruta del trigo - Rubio Vela, Agustín (Caplletra. Revista Internacional de Filologia, 2002)
The author shows how cereal imports from southern Aragon into the Valencian kingdom encouraged contactbetween medieval Valencians and Aragon. Through the documents collected, we can observe the links betweensouthern Aragon and Valencia, discover the specific geographics of such contacts, and see how the arrival ofimported products opened the path for the penetration of Aragonese linguistic material. The paper also offers anumber of Aragonese toponyms adapted into Catalan, drawn from the documents presented.